The Impact of Job Stress, Job Satisfaction and Job Burnout on Turnover Intention among Project Management Team Members in Industrial Cities in The Kingdom of Saudi Arabia - Badawi, Maher; AlOtaibi, Abdullah; AlOtaibi, Sultan (The Arab Journal of Administration, 2023)
This research is aiming to figure out the impact of job stress, job satisfaction and job burnout on turnover intention among project management team members in industrial cities in the kingdom of Saudi Arabia. The research sample consisted of 212 respondents and the data were collected using electronic questionnaires. Statistical procedures were applied using SPSS (means, standard deviations, correlation analysis, reliability analysis) and AMOS (Path analysis). The research findings showed that there are positive relationships between job burnout and turnover intention and between job stress and job burnout. The findings showed a negative relationship between job burnout and job satisfaction and between job satisfaction and turnover intention. The findings showed a positive relationship between job burnout and turnover intention. The results of this research can be used as a reference for industrial fields in the Kingdom of Saudi Arabia to improve the public awareness and enhance the organizational efficiency.